A Bayesian approach to determine the impact of institutions on the unemployment rate - Andreas Sachs (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
Labor and product market regulations affect the unemployment rate of a country without doubt. Econometricians, however, have yet to establish an unequivocal significance of this impact. Model mis-specification, one of the main underlying problems, is overcome by adopting a Bayesian Model Averaging approach. I apply this method to a panel data set that covers 17 OECD countries for the time period from 1982 to 2005 and for up to 20 potential explanatory variables. 8 institutional indicators are identified as significant determinants of unemployment. Endogeneity due to reverse causality is also considered by applying an instrumental variable estimation approach.
Keywords: C33; E02; E24; 330; unemployment; institutions; labor and product markets; model averaging; Arbeitslosigkeit; Arbeitsmarktflexibilisierung; Regulierung; Institutionalismus; Panel; Modell-Spezifikation; Bayes-Statistik; Schätzung; OECD-Staaten